Strategi Menjadi Pemimpin Bagi Generasi Milineal di Era Komunikasi Digital - Meydita Asima Megarani Simbolon (MUKASI: Jurnal Ilmu Komunikasi, 2023)
A leader's leadership style, both in an organization and in a company, is one of the absolute tips for achieving the vision and mission that has been prepared. A leader must be able to plan and then move all relevant individuals to collaborate in such a way as to achieve optimal organizational goals. The presence of the millennial generation is now starting to dominate in various organizations/institutions because the millennial generation has entered productive ages, requiring them to work and organize. So being a leader of the millennial generation is a big challenge. The millennial generation's familiarity with digital communication technology can be used as a strategy for communication patterns in organizations where most employees are from the millennial generation. Leaders are expected to continue to update and follow digital media developments and be able to apply them in organizational communication. The research method used is the study of literature (literature) which discusses leadership strategies, organizational communication and the millennial generation. Leaders in the millennial era must be able to become connectors, mentors, and openers of opportunities and challenges, as well as digital literacy.